The role of information in the information society - Lazarević Sofija (Megatrend Revija)
The first part of the paperwork deals with the analysis of the concept and the role of information in the information society. The concept of information as we use it in everyday language plays a central role in modern society. It is common to consider information as a basic condition for economic development along with capital, labor, and raw materials, but what makes information particularly important in the present is its digital nature. The difference between information, data and knowledge is presented. The focus of the second part of the paperwork is the information society. The information society is a concept that emphasizes the use of information and information technologies in almost all areas of society. It is considered the successor of the industrial society. The information society is managed by knowledge, expertise and only informed decisions and actions. It requires and promotes clarity, precision, honesty and openness. Closely related concepts are post-industrial society, postfordism, postmodern society, knowledge society, telematics society, information revolution and network society.